Optical spectroscopic studies of simple polyenes and complex xanthophylls - Galinato, Mary Grace I. (ProQuest Information and Learning Company, 2007)
The optical spectroscopic properties of four polyenes, decatetraene, dodecapentaene, tetradecahexaene and hexadecaheptaene, two carotenes, I_2-carotene and lycopene, and five xanthophylls, neoxanthin, violaxanthin, lutein, zeaxanthin, and I_2-cryptoxanthin, were studied using steady-state absorption, fluorescence, fluorescence excitation or ultrafast transient absorption spectroscopy. High-performance liquid chromatography (HPLC) was carried out immediately prior to the spectroscopic experiments to obtain isomerically pure molecules. In the first part of the study, experiments on the polyenes were done at cryogenic temperatures in n-alkane mixed crystal solvents and provided enhanced spectral resolution compared to room temperature solutions and low-temperature glasses. This allowed discrimination of emission from cis and all-trans isomers. At 77 K, cis isomers of the polyenes displayed significantly more intense emission from the S1 (21A g-) state than observed for the all-trans isomers. In addition, the cis isomers exhibited spectral features associated with the forbidden S0 (11A g-) a_#x86;#x92; S1 (21Ag -) transition. The effect of solvent polarizability on the S 1 (21Ag-) and S2 (11Bu+) energies of the all- trans polyenes was systematically evaluated. Upon extrapolation to zero polarizability, the values were found to be in close agreement with gas phase measurements. The experimental determinations were compared with theoretically-obtained values from the literature. In the second part of the study, spectral properties of the more complex carotenes and xanthophylls were investigated in solution using steady-state absorption spectroscopy in the visible and near-infrared (NIR) spectral regions. Also, cation radicals of the molecules were generated chemically and their spectra were interpreted using quantum computations. Finally, the steady-state and ultrafast transient absorption spectroscopic features of violaxanthin and zeaxanthin were investigated in solution, in pigment-protein complexes prepared from Photosystem II (PSII), and in isolated thylakoids. The goal of this part of the work was to pinpoint the location of zeaxanthin cation radical formation thought to be a component in excess energy dissipation in higher plants.